2016
DOI: 10.1097/bsd.0b013e31827566a8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Radiologic Changes After Microsurgical Bilateral Decompression by a Unilateral Approach in Patients With Lumbar Spinal Stenosis and Grade I Degenerative Spondylolisthesis With a Minimum 3-Year Follow-Up

Abstract: Despite small case series with retrospective design and the absence of a control group, our study suggests that bilateral decompression via a unilateral approach in patients with LSS and grade 1 DS showed good mid-term clinical outcomes, despite an increase in slip percentage.However, more marked increases in slippage were observed in patients with sagittal motion in spondylolisthesis levels on preoperative dynamic x-ray, than in patients without sagittal motion. Therefore, bilateral decompression via a unilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 17 publications
2
22
0
6
Order By: Relevance
“…These modifications are intended to safeguard spinal stability by preserving the midline supporting structures, such as spinous processes and interspinous ligaments, while decompressing the central and lateral areas of the surgical level. Adequate decompression and its relation to a good surgical outcome have been reported5,9,20). These approaches do have some technical and theoretical limitations.…”
Section: Discussionmentioning
confidence: 99%
“…These modifications are intended to safeguard spinal stability by preserving the midline supporting structures, such as spinous processes and interspinous ligaments, while decompressing the central and lateral areas of the surgical level. Adequate decompression and its relation to a good surgical outcome have been reported5,9,20). These approaches do have some technical and theoretical limitations.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce surgical invasiveness, various less invasive techniques have been developed [1,3,[12][13][14], and comparative studies have shown that less invasive surgeries have benefits compared to conventional surgeries in relation to operative time, estimated blood loss, lumbar muscle destruction, and complications. Among patients with spondylolisthesis who underwent less invasive decompression surgery, Mori et al [15] revealed that there was a significant increase in the percentage of slip at postoperative year 2, and some previous studies pointed out risk factors for postoperative slippage [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Die Behandlung kann jedoch auch mit einigen Risiken verbunden sein. Die meisten Probleme ergeben sich durch eine entstehende Hypermobilität der Wirbelsäule, welche zusätzliche Schmerzen verursachen kann und einen negativen Effekt auf die benachbarten Segmente hat [17,18]. Die Abtragung von posterioren Strukturen während der Dekompression kann zu einer erhöhten biomechanischen Instabilität der Wirbelsäule führen.…”
Section: Adverse Eventsunclassified